BANGUNAN REKREASI BERTEMAKAN ALAM-NATURAL WELLBEING RETREAT - Salman Airlangga (Jurusan Arsitektur dan Perencanaan, 2020)
Nature Themed Recreational Building-Natural Wellbeing Retreat is designed to help fulfill the daily and dynamic needs of the people through a natural concept focused on wellbeing that is aimed to answer the problems of the Sunter district such as high levels of stress, low amount of green open spaces, and the abundance of the retiree using a Pattern-Based method with the main focus being the space and site. Natural Wellbeing Retreat can be interpreted as an action to return to nature to replenish happiness and health. Humans require recreation and rest from daily routines and business forced upon them. Recreation/rest time can lead to a meeting between creative humans to build a more innovative and productive community. Therefore a wellbeing theme is taken where all the programs will be injected with the primary objective of the project, which is to maintain the mental, physical, and emotional health of its users by also applying natural aspects related to gardens/parks which are useful in creating a happier community which is also by a selected location that lacks green open areas. This natural aspect will be further supported by the background of Lake Sunter as a blue open space. Keywords: Nature; Recreation; Retiree; StressAbstrakBangunan Rekreasi Bertemakan Alam-Natural Wellbeing Retreat hadir untuk membantu kehidupan serta menjawab kebutuhan masyarakat yang dinamis melalui tema yang akan diangkat berupa Natural Wellbeing Retreat yang ditujukan untuk menjawab masalah-masalah utama kawasan Sunter seperti tingginya tingkat stres, kurangnya ruang terbuka hijau, dan banyaknya pensiunan menggunakan metode desain berbasis pola dengan memperhatikan obyektifitas ruang dan tapak. Natural Wellbeing Retreat dapat diartikan sebagai suatu tindakan untuk kembali ke alam agar bahagia dan sehat. Kami membutuhkan suatu rekreasi atau waktu istirahat dari segala rutinitas dan kesibukan yang dituntutkan pada mereka. Waktu rekreasi/istirahat ini bisa mengarah kepada pertemuan antar manusia-manusia kreatif dan membangun komunitas yang lebih inovatif serta produktif. Maka dari itu diambillah tema wellbeing dimana seluruh program akan disuntikan tema ini dengan tujuan utama proyek yaitu menjaga kesehatan mental, fisik, serta emosional para penggunanya dengan juga menerapkan aspek natural yang berkaitan dengan gardens/parks yang efektif untuk menciptakan komunitas yang lebih bahagia dan juga sesuai dengan lokasi terpilh yang kekurangan area terbuka hijau. Faktor alami ini akan terlebih lagi didukung dengan adanya latar belakang Danau Sunter sebagai ruang terbuka biru.